Dos experiencias de encierro en el ASILO del Buen Pastor de Montevideo: 1929-1934 - Facundo Álvarez Constantín (IdeAs)
This article analyzes the experience of two young women who passed through the ASILO del Buen Pastor in Montevideo between 1929 and 1934. Their particularity was to write letters from various institutions with the aim of denouncing mistreatment, transmitting difficult experiences, requesting "the capacity", among other. The objective pursued by this text is, on the one hand, to give a voice to young people regarding their passage through the Asylum and, on the other, to understand the existence of the letters inserted within an institutional, state bureaucratic context. My hypothesis is that their texts were a legitimate tool and a valid resource that young people knew how to use in order to modify their reality and to express their feelings and emotions. María Luisa and Fermina were just two of the young women who wrote their letters at the conjuncture of the late 1920s in Uruguay. This article takes other experiences of women who also wrote in similar contexts and is included with the aim of increasing the number of testimonies and giving legitimacy to the experiences of María Luisa and Fermina. I take the perspective of gender and age because they are useful in that they allow us to elucidate the differences regarding their condition as minor women – according to the Civil Code – and confined in destruction centers and, in turn, help to make visible the perpetuation of hierarchies in the society. Finally, the article proposes a look that privileges the voice of young people over the will of the authorities and that values their ability to write to change their reality.